Response to Medication Dosing Alerts for Pediatric Inpatients Using a Computerized Provider Order Entry System - Perlman, S.L.; Fabrizio, L.; Shaha, S.H.; Magid, S.K. (Applied Clinical Informatics, 2011)
Objective: Medication dosing errors are of particular concern in hospitalized children. Avoidance of such errors is essential to quality improvement and patient safety. Computerized provider order entry (CPOE) systems with clinical decision support (CDS) have the potential to reduce medication errors. The objective of this study was to evaluate provider response to the dosing alerts in a CPOE system with CDS for pediatric inpatients and to identify differences in provider response based on clinician specialty.Patients and methods: We conducted a retrospective analysis of all medication dosing alerts over a 1-year period (January 1 through December 31, 2008) for all pediatric inpatients at Hospital for Special Surgery. Alerts were analyzed with respect to medication dosing, prescriber, and action taken by the prescriber after the alert was triggered (i.e., accepted suggested change, ignored recommendation/overrode, or cancelled the order).Results: During the study period, 18,163 medication orders were placed and 1,024 dosing alerts were fired. Overdosing of medications accounted for 91% of the alerts and underdosing 9%. The pediatric-trained providers ignored more alerts and cancelled fewer orders than the non-pediatric-trained providers (p<0.001). Both groups changed the order similarly based on CDS recommendations.Conclusions: Differences in response to CDS were found between pediatric-trained and non-pediatric-trained providers caring for pediatric patients; however, both groups changed orders based on CDS similarly. CPOE with built-in CDS may be of particular value when providers with different specialties and types of training are caring for pediatric patients.
Keywords: ADE; adverse drug events; CDS; clinical decision support; CIS; clinical information system; CPOE; computerized provider order entry